Prebiotic fructooligosaccharides ameliorate the lipop olysaccharides-induced oxidative stress of mice brain - Shreya, Banalata Mohanty (Journal of Applied Pharmaceutical Science, 2024)
A bacterial endotoxin called lipopolysaccharide (LPS) causes brain oxidative stress, which in turn causes neurotoxicity and psychological disorders. In the current investigation, the pharmacological effects of prebiotic fructooligosaccharides (FOS) were assessed in mice brains that had undergone oxidative stress induced by LPS. Eight-week-old female adult Swiss albino mice were maintained in six groups: Group I as control and LPS (1 mg/kg bw) was administered intraperitoneally to Groups II–IV. FOS supplementation was given through oral gavaging to Group III (2 g/kg bw) and IV (4 g/kg bw) for 4 weeks following a 5-day LPS exposure, but not to Group II. Group V (2 g/kg bw) and VI (4 g/kg bw) received FOS for 4 weeks. Results showed that the LPS-induced brain oxidative stress by increasing malondialdehyde (MDA) and oxidized glutathione (GSSG) content, whereas decreased the antioxidant defence enzymes activity. After FOS supplementation, LPS-induced oxidative stress was modulated in a dose-dependent way by decreasing levels of MDA, and GSSG, and increased antioxidant defence enzyme activity such as glutathione reductase, catalase, superoxide dismutase, total, and reduced glutathione. Moreover, the FOS modulated the LPS-led decreased body and brain weight to control level. Thus, the antioxidative property of FOS modulates the LPS-induced oxidative stress of mice brains.
Keywords: Lipopolysaccharide, neurotoxicity, oxidative stress, prebiotics, fructooligosaccharides